Increased Calcitonin Gene-Related Peptide Expression in DRG and Nerve Fibers Proliferation Caused by Nonunion Fracture in Rats - Kasai Y (Dove Medical Press, 2021)
Yusuke Kasai, Koji Aso, Masashi Izumi, Hiroyuki Wada, Junpei Dan, Yoshinori Satake, Toru Morimoto, Masahiko Ikeuchi Department of Orthopedic Surgery, Kochi Medical School, Kochi University, Nankoku, 783-8505, JapanCorrespondence: Koji AsoDepartment of Orthopedic Surgery, Kochi Medical School, Kochi University, 185-1 Oko-cho Kohasu, Nankoku, 783-8505, JapanTel +81-88-880-2386Fax +81-88-880-2388Email koji.aso@gmail.comPurpose: Nonunion bone fracture can be a cause of persistent pain, but the pathophysiology remains largely unknown. The objective of this study was to identify how nonunion affect persistent pain after fracture. Specifically, we evaluated the association of neuropeptide change in dorsal root ganglia (DRG) and nerve proliferation at fracture sites with pain.Methods: Rat union and nonunion fracture models were created. A piece of latex glove was placed at the fracture site to create a nonunion model. At 6 weeks after surgery, bone healing was assessed using radiography. In addition, the presence of calcitonin gene-related peptide-immunoreactive (CGRP-IR) DRG at the level of L3 and anti-growth associated protein 43-immunoreactive (GAP43-IR) nerve fibers in the scar tissue between the bone fragments were evaluated. Pain-related behavior was assessed using forced treadmill running.Results: In radiological images at 6 weeks after surgery, callus formation was formed continuously between bone fragments in the union models. On the one hand, a clear gap was detected between fragments in nonunion models. The percentage of CGRP-IR DRG cells and the density of GAP43-IR nerve fibers in the scar tissue between the bone fragments in nonunion models was significantly higher than that in union models (p < 0.05). An increase in inflammatory cell infiltrate was observed in scar tissues in the nonunion models. During forced treadmill running, rats in the union model could run significantly longer than those in the nonunion models.Conclusion: Increased CGRP expression in DRG cells and abnormal nerve proliferation secondary to prolonged inflammation could lead to persistent pain after bone fracture. In clinical practice, early achievement of bone union may minimize the development of persistent pain after fractures.Keywords: fracture pain, nerve proliferation, nonunion of fractures